ANALISA RUGI-RUGI ANTENA PEMANCAR FM ISTAKALISA YOGYAKARTA - Priyambodo, Sigit (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
Everyone basically knows and perceives about the function of antenna. The antenna is a tool or device which has function to receive and transmit signals from a point to another. According to the research of IstaKalisa’s FM Transmitter Radio antenna of Yogyakarta, the writer will give conclusion of research. Loss which affect the working of transmitting radio stations are loss of cord, loss of space damping, and loss of resistance. They make fading on the transmitting power where the fading is in dB unit. Moreover, the position and location of Istakalisa FM transmitter radio station is in the downtown. It does not support to the transmitting system caused by ground conductivity is less than standard and also numbers of high buildings.